Respuesta :

Answer:

The simplified expression is:

[tex]\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)=0.2y+0.2x-8[/tex]

Step-by-step explanation:

Given the expression

[tex]\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)[/tex]

[tex]\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a[/tex]

[tex]=\frac{2}{5}y+\frac{1}{5}x-0.2y-6-2[/tex]

[tex]\mathrm{Group\:like\:terms}[/tex]

[tex]=\frac{2}{5}y-0.2y+\frac{1}{5}x-6-2[/tex]

Add similar elements

[tex]=0.2y+\frac{1}{5}x-6-2[/tex]

[tex]=0.2y+\frac{x}{5}-6-2[/tex]

[tex]=0.2y+\frac{x}{5}-8[/tex]

[tex]=0.2y+0.2x-8[/tex]

Thus, the simplified expression is:

[tex]\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)=0.2y+0.2x-8[/tex]